Mengurai Benang Kusut Indikasi Kematian Massal Eksistensi Tuhan di Abad Globalisasi - Nurul Anam (Universitas Islam Negeri Mataram, 2009)
The “post god” era represents a period indicating about mass death of god and describing a human life that existentially